Spatial aliasing effects on beamforming performance in large-spacing antenna array - Suroso, Dwi Joko; Gautam, Deepak; Sunarno, Sunarno (Communications in Science and Technology, 2019)
In the next wireless communication generation, 5G, it is obvious to employ the half-spacing antenna elements as high-resolution antenna array. However, to compensate the lower aperture from short-spacing elements, the number of antennas should be grown larger. It will be costly and increase complexity in terms of antenna array analysis. In this paper, the aliasing effects on beamforming of antenna array geometry utilizes inter-element spacing more than half-lambda. The antenna geometry of linear, circular and planar will be explored in this paper and the center frequency for simulation is 60 GHz. It is also due the fact that many researchers on 5G believe 60 GHz will be employed as 5G frequency band. 60 GHz is truly higher than today Long-term-evolution (LTE) working frequency and it is really challenging to its signal model due to small wavelength and its effective signal working distance as effect of rain attenuation, etc. As our preliminary results, linear array, which only considers the azimuthal, the spatial aliasing appears in the inter-element distance more than 1-lambda. The circular and planar consider the azimuth and elevation properties of incoming signals. In circular array, the power angular of a signal can be detected accurately applying the 3-sector antenna pattern. When the inter-element distance grows more than 1.5 lambda, the spatial aliasing which appear to be side lobe with similar power angular dominate the incoming signal detection. The result shows us that employing the 2-lambda distance or more will be useless. Planar array which actually a 2-axis linear array give unexpected results, most of detections are inaccurate and power angular also low. This concludes that spatial aliasing effects will degrade the beamforming performance due to confusion between real signal and fake signal resulting from similar values of array factor.